Socio economic status and food insecurity among the elderly in Panji District, Kota Bharu Kelantan, Malaysia - Mohd Nor, Fadilah; Sulaiman, Norhasmah; Mohd Shariff, Zalilah; Ibrahim, Zuriati (Malaysian Consumer and Family Economics Association, 2017)
Food insecurity is a common problem among the low-income households in the developing countries including Malaysia. This study was to assess the prevalence of food insecurity and identify the risk factor of food insecurity among elderly in Panji District, Kota Bharu, Kelantan, Malaysia. Face-to-face interview was done among 227 elderly aged 60 and above to obtain their information on demographic and socio-economic background, and food security status. For analysis of data, descriptive statistics, chi-square, ANOVA and logistic regression were used. The findings indicated that 22.9% of the elderly were food insecure which comprised of 15.4% low food secure, and 7.5% were very low food secure. There were significant differences between food security status with personal income of elderly, household size, marital status, educational level, and age (p<0.05). There was a significant decrease in the mean income as food security status worsened (p<0.05). Household size more than five members and income less than RM1000 were more likely to become food insecure. Food insecurity in the elderly is worse than in other populations. Future intervention and assistance program should focuses more on economic status among the elderly to reduce the risk of food insecure.